2006
DOI: 10.1152/jn.01265.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Effects of Brief Daily Periods of Unrestricted Vision During Early Monocular Form Deprivation

Abstract: Experiencing daily brief periods of unrestricted vision during early monocular form deprivation prevents or reduces the degree of resulting amblyopia. To gain insight into the neural basis for these "protective" effects, we analyzed the monocular and binocular response properties of individual neurons in the primary visual cortex (V1) of macaque monkeys that received intermittent unrestricted vision. Microelectrode-recording experiments revealed significant decreases in the proportion of units that were domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…This conclusion was supported by the limited set of data from a third cohort that received 12-h daily visual exposure. Remarkable support was also provided by the results of a study on monkeys that employed a 12-h period of total visual exposure each day (Sakai et al, 2006;Wensveen et al, 2006). The monkeys were maintained in a colony room on a 12-h light-dark cycle from approximately 3 to 21 weeks of age during which time they received mixed visual input on a daily basis.…”
Section: Discussionmentioning
confidence: 85%
“…This conclusion was supported by the limited set of data from a third cohort that received 12-h daily visual exposure. Remarkable support was also provided by the results of a study on monkeys that employed a 12-h period of total visual exposure each day (Sakai et al, 2006;Wensveen et al, 2006). The monkeys were maintained in a colony room on a 12-h light-dark cycle from approximately 3 to 21 weeks of age during which time they received mixed visual input on a daily basis.…”
Section: Discussionmentioning
confidence: 85%
“…Our finding that the absolute amount of daily binocular experience has a greater bearing on the cortical territory occupied by the two eyes supports the conclusion that a certain minimum of daily normal vision is necessary and sufficient to maintain a normal V1 architecture. Two previous studies that reported a beneficial effect of daily binocular experience employed either a single predominantly binocular exposure paradigm (Olson & Freeman, 1980) or a limited number of exposure paradigms (with a fixed total daily exposure) followed by a 3‐year period of recovery before physiological recording, which further complicated the interpretation of the data (Sakai et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…D), is not closely linked to ocular dominance shifts in V1 and that deficits in some monocular receptive field properties may be more predictive of the vision loss (Kiorpes et al, ; Kiorpes and Movshon, ). However, a few other studies have reported that even monocular receptive field properties in V1 are largely normal despite vision loss following early strabismus (Smith et al, ; Sakai et al, ; Bi et al, ). Whatever the case, an ocular dominance imbalance—as hypothesized based on Wiesel and Hubel's early work—does not appear to directly determine the existence or extent of vision loss that results from early abnormal visual experience.…”
Section: Introductionmentioning
confidence: 99%